Experimental Investigation of Ultrasonic Cavitation Erosion: Implications for Water Turbines and Hydraulic Machinery - Kevorkijan, Luka; Jernejc, Tilen; Lešnik, Luka; Biluš, Ignacijo (International Conference Fluid Power 2025: Conference Proceedings, 2025)
Cavitation erosion is a major concern in water turbines and hydraulic machinery, where bubble collapse near solid surfaces leads to material degradation and reduced efficiency. In this study, ultrasonic cavitation tests were conducted using a Sonics VCX-750 ultrasonic vibratory apparatus operating at 20 kHz to investigate erosion behaviour of aluminium and steel specimens under identical conditions. The sonotrode tip was submerged 30 mm below the water surface, with amplitude of 30 µm and fluid temperature maintained at 17 °C. High-speed imaging at 100,000 frames per second captured bubble dynamics. After 3 hours of exposure, surface photographs revealed significantly more extensive erosion on aluminium compared to steel, demonstrating higher resistance of the latter to cavitation. The results highlight the importance of material selection in hydraulic applications and provide insights into cavitation mechanisms relevant to the durability and performance of water turbines.